Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays Saccharata) Terhadap Pemberian Pupuk Kandang Sapi dan Pupuk Organik Cair - Sitepu, Nico Armanda; Luta, Devi Andriani; Harahap, Ariani Syahfitri (JURNAL AGROPLASMA, 2025)
Efforts that can be made to increase corn productivity are by adding organic materials from plant residues and animal waste to the soil. This study aims to determine the effect of cow dung and liquid organic fertilizer from agricultural waste and their interactions on the growth and production of corn plants. This study used a Randomized Block Design with 2 factors and 3 replications to obtain 48 research plots. Factor I cow dung with the symbol "S" consists of 4 levels, namely: S0 = 0 g, S1 = 200 g, S1 = 300 g, S1 = 400 g. Factor II liquid organic fertilizer from agricultural waste with the symbol "P" consists of 4 levels, namely: P1 = 100 ml, P2 = 200 ml, P3 = 300 ml, P4 = 400 ml. The parameters observed in this study were plant height, number of leaves, flowering age, weight per plot, cob length, cob diameter. The results of the study showed that the provision of cow dung and liquid organic fertilizer had a very significant effect on all observation parameters. Interaction had no significant effect on all observation parameters. Keywords: cow dung, agricultural waste, sweet corn